Thymic Microenvironment Is Modified by Malnutrition and Leishmania infantum Infection - Losada-Barragán, Monica; Umaña-Pérez, Adriana; Durães, Jonathan; Cuervo-Escobar, Sergio; Rodríguez-Vega, Andrés; Ribeiro-Gomes, Flávia L.; Berbert, Luiz R.; Morgado, Fernanda; Porrozzi, Renato; Mendes-da-Cruz, Daniella Arêas; Aquino, Priscila; Carvalho, Paulo C.; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Detrimental effects of malnutrition on immune responses to pathogens have long been recognized and it is considered a main risk factor for various infectious diseases, including visceral leishmaniasis (VL). Thymus is a target of both malnutrition and infection, but its role in the immune response to Leishmania infantum in malnourished individuals is barely studied. Because we previously observed thymic atrophy and significant reduction in cellularity and chemokine levels in malnourished mice infected with L. infantum, we postulated that the thymic microenvironment is severely compromised in those animals. To test this, we analyzed the microarchitecture of the organ and measured the protein abundance in its interstitial space in malnourished BALB/c mice infected or not with L. infantum. Malnourished-infected animals exhibited a significant reduction of the thymic cortex:medulla ratio and altered abundance of proteins secreted in the thymic interstitial fluid. Eighty-one percent of identified proteins are secreted by exosomes and malnourished-infected mice showed significant decrease in exosomal proteins, suggesting that exosomal carrier system, and therefore intrathymic communication, is dysregulated in those animals. Malnourished-infected mice also exhibited a significant increase in the abundance of proteins involved in lipid metabolism and tricarboxylic acid cycle, suggestive of a non-proliferative microenvironment. Accordingly, flow cytometry analysis revealed decreased proliferation of single positive and double positive T cells in those animals. Together, the reduced cortical area, decreased proliferation, and altered protein abundance suggest a dysfunctional thymic microenvironment where T cell migration, proliferation and maturation are compromised, contributing for the thymic atrophy observed in malnourished animals. All these alterations could affect the control of the local and systemic infection, resulting in an impaired response to L. infantum infection.